ISU MENGENAI POLA PIKIR YANG MENJADI TANTANGAN PERUSAHAAN DALAM MENERAPKAN CORPORATE SUSTAINABILITY MANAGEMENT - Failasufa, Nadhia (Jurnal Akuntansi AKUNESA, 2014)
Corporate Sustainability Management is needed as a business approach that creates long term shareholder value. The implementation of sustainability is conducted by integrating the economic, social and environmental aspects. The purpose of this study is to respond the issue of mindset which is raise doubt in implementation of corporate sustainability management. This exploratory study results that implementation of sustainability will provide continuing development for companies to stimulate innovation, improve relations with the local community, improve efficiency and productivity and differentiate itself from competitors in the very tight competition market.   Keyword: Corporate Sustainability Management, challenge, mindset issue